Arab American parents' perceptions of their children's experience in the USA: a qualitative study. Issue 7 (3rd July 2017) - Ahmad, Jamal
ABSTRACT: The purpose of this study was to examine Arab American parents' perceptions of difficulties their children experience in the USA. Both Arab American children born outside the USA who later moved to the country and children born in the USA to Arab parents were examined. Fifty Arab American families were interviewed in two areas in the State of Michigan. Data were translated from Arabic to English, and then analysed according to specific themes. Results revealed that the most common difficulties are language acquisition and emotional and social adjustments. The least frequent problem is using technology. Additionally, results showed that children who live in concentrated populations of Arab immigrants have fewer problems than those who live in less concentrated areas. The implications of results for educators, school psychologists and new Arab immigrants are presented.